Design and application of an endotracheal tube fixation belt (一种气管插管固定寸带的设计与应用) - WEI An (魏安); SUN Xiumei (孙秀梅); YUAN Guowei (袁国伟); JI Ya (纪亚) (中西医结合护理)
Tracheal intubation is an indispensable mean of life support in the rescue of critically ill patients, which can effectively improve patients' hypoxemia and tissue hypoxia and promote oxygenation function. Unplanned tracheal extubation is one of the common and serious complications in patients with mechanical ventilation, and improper catheter fixation is an independent risk factor leading to unplanned extubation. Therefore, good fixation measures are essential to prevent unplanned extubation. This study introduces the design and use method of a utility model of endotracheal tube fixation belt, which effectively improves the fixation quality of endotracheal tube and patient comfort in tracheal intubation (气管插管是抢救危重症患者不可或缺的生命支持手段, 其能够有效改善患者的低氧血症和组织缺氧, 促进氧合功能。非计划性气管拔管是机械通气患者中常见且严重的并发症之一, 导管固定不当是导致非计划性拔管的独立风险因素, 因此, 良好的固定措施对于预防非计划性拔管至关重要。本研究介绍了一款实用新型气管插管固定寸带的设计和使用方法, 其有效提高了气管插管的固定效果, 同时减轻了医护人员的工作负担, 提高了工作效率, 增加了患者的舒适性。)